The Effect of Additional TiO2 Nanofluid on Heat Transfer Rate and Thermal Resistance on Processor Cooling with Ultrasonic Vibration - Dhiya'ul Ro'id Alfaris; Sudarmadji Sudarmadji (Department of Mechanical Engineering, Universitas Andalas, 2022)
The cooling system is very important for cooling the processor to keep it at working temperature. According to Moore's law, the processor doubles every 24 months. This has an impact on the power consumed by the processor will increase, along with increasing power, the heat emission generated will also increase. So a water cooling system is needed to overcome these problems in the future. The addition of nanofluid to the cooling medium and the provision of ultrasonic vibration treatment are expected to maximize cooling performance. The purpose of this study was to determine the effect of the addition of TiO2 nanofluid and ultrasonic vibration on the overall heat transfer coefficient and thermal resistance, and then compare them with conditions without vibration. The method used is an experimental method with various concentrations of TiO2 nanofluid 0.1%, 0.15%, and 0.2%. The power consumed by the processor is simulated using a heater with variations of 150W, 200W, and 250W. An ultrasonic transducer is added to the radiator to provide a vibration frequency of 40 KHz. The result of this research shows that the U value of aquadest bottom fluid with vibration increases from 2834.563579 W/m2.oC becomes 3283.473891 W/m2.oC or 15.84%. Nanofluid TiO2 0,1% with vibration increased from 3419.874768 W/m2.oC to 4109.319539 W/m2.oC or 20.16% The effect of nanofluid concentration increased from 4029.871937 W/m2.oC becomes 5534.745283 W/m2.oC or 37.34% and the Rth value of aquadest base fluid with vibration decreased from 0.1588 oC/W to 0.1508 oC/W by 4.99%. Nanofluid TiO2 0,15%with vibration decreased from 0.0895 oC/W to 0.0813 oC/W or 9.22%. The effect of nanofluid concentration decreased from 0.11275 oC/W to 0.073 oC/W or 35.25%.